Heat Pump Assisted Clothes Dryer - Yeap, Seng Chye (Universiti Sains Malaysia, 2003)
A clothes drying in humid tropic is an energy intensive process. In densely built-up urban areas with many high rise apartments this is a more acute problem. Restricted air flow across the dense area, limited solar exposure and round the year humid climate make the drying process less effective. In the present research, a Heat Pump Assisted Clothes Dryer was designed and developed to study the feasibility of drying clothes using waste heat of a condenser of a typical split type domestic air conditioner. Two modes of heat pump drying have been studied - the open system, and the close system. In the open system drying was done by condenser heat only whereas in the closed system the air was dehumidified by the evaporator prior to being heated by condenser heat. Three additional modes of drying were also tested to compare their relative performances vis a vis open and close system drying. These are heating by solar radiation, heating with electrical bulbs and electrical heating elements. This investigation found that drying clothes in the open system heat pump drying mode is far better than the other modes. For experiment without solar exposure, it only took 45 minutes to dry 1.993 kg bone dry specimen clothes. It also has the highest drying rate of 0.724 kg/h compared to 0.117 kg/h for natural drying and 0.523 kg/h for close system heat pump drying. Time required for open system heat pump drying was only 16.36 % that of natural drying and 69.23 % that of close system heat pump drying. Supplementing the drying process by solar radiation improves the drying rate. The drying rate improves to 0.847 kg/h for open system heat pump, 0.316 kg/h for natural drying and 0.523 kg/h for close system heat pump drying. With solar flux, the drying time is only 35 minutes for open system heat pump drying, which is only 35 % of natural drying and 58.33 % of close system heat pump drying. The results of the investigation show that heat pump assisted drying using condenser heat is a practical and economical option of utilising waste heat gainfully.